Governance, forests and REDD+ in Latin America - Petkova, E.; Larson, A.M.; Contreras Hermosilla, A.; Toni, F. (Center for International Forestry Research, 2010)
The implementation and success of REDD+ strategies, plans and projects will depend on whether REDD+ influences governance or is shaped by existing governance failures. As governments prepare for REDD+ implementation, they should: – address faulty forest policies and revise development and market policies affecting forests to ensure that gains through carbon emissions reduction in one sector are not counterbalanced by losses in another; – establish a balance between central oversight and decentralised decision-making, tenure security and transparent benefit-sharing arrangements to ensure the legitimacy of REDD+ and avoid conflicts; – build capacity to implement and enforce the law and reduce forest crime through adequate funding levels, independence from both political and industry influence, and legal and regulatory clarity and stability. Achieving the necessary policy reform is a politically difficult process likely to meet resistance. However, it provides an opportunity to shift development patterns and reduce deforestation and degradation. Although civil society and external actors, including donors, can be important drivers for reform, ultimately, it will require policymakers and civil